GREWAR, David McKenzie [Dawie] Inventory of documents - GREWAR, David McKenzie [Dawie] (ARCA, 2018)
Private papers of D.M. Grewar, Commissioner General of the South Sotho Ethnic Unit, Member of the President's Council.
COVERAGE 1958-1993; 59 Files; 0,33 Metres.
Keywords: GREWAR, David McKenzie [Dawie]; Inventories; Politicians; National Party